Potential use of functional bacteria from tropical rehabilitated forest as bio-fertilizer - Tang, Amelia (2017)
Rehabilitated forests are established in an effort to overcome the threat of major soil degradation and erosion. Soil cellulolytic, nitrogen-fixing (N-fixing), and phosphate-solubilizing microorganisms are very important functional microbial groups in regulating the elemental cycle, and plant nutrition in forest soil. Bacteria, reflected by their major abundance among microbial groups, make up a large constitution of biodiversity in soils, and they participate in soil key processes which eventually impact the whole terrestrial ecosystems operations. Relationship between soil cellulolytic, N-fixing, and phosphate-solubilizing bacterial counts, and forest stand ages of 4, 9, 14, and 19 were assessed as means to evaluate soil health of planted forests. All cellulolytic, N-fixing, and phosphate-solubilizing populations showed linear relationships with forest age. These functional bacterial populations demonstrated good potential to be adopted as soil health indicators in the rehabilitated forest. Assessment of functional bacterial population sizes should be ongoing with forest stand succession for better understanding their relationships, and growth trends. Out of 15 functional isolates, cellulolytic isolate Serratia nematodiphila C46d, N-fixing isolate Burkholderia nodosa NB1, and phosphate-solubilizing isolate Burkholderia cepacia PB3 with outstanding plant growth-promoting (PGP) activities were selected for a pot trial. The treatments evaluated in the pot trial were: 1) control with no bacterial inoculation, and no chemical fertilizer (Control); 2) no bacterial inoculation but with compost, and chemical fertilizer combination at 50% fertilization level (OM); 3) inoculation with C46d, and with compost and chemical fertilizer combination at 50% fertilization level (TC); 4) inoculation with NB1, and with compost, and chemical fertilizer combination at 50% fertilization level (TN); 5) inoculation with PB3, and with compost, and chemical fertilizer combination at 50% fertilization level (TP); 6) inoculation in consortium of C46d, NB1, and PB3, with compost, and chemical fertilizer combination at 50% fertilization level (TCNP); and 7) control with no bacterial inoculation, and no compost, but only with chemical fertilizer at 100% fertilization level (Chemical Fertilizer). Cellulolytic population was highest at all bacterial treatments; N fixers dominant in TN, TP, and TCNP whereas phosphate-solubilizers fluorished in TP and TCNP. Only N fixers demonstrated significant effects on plant biomass, from positive relationships with plant N and P uptake. This present study indicated presence of some efficient and effective cellulolytic, N-fixing, and phosphate-solubilizing bacterial species among the natural rhizobacterial community in soils of tropical rehabilitated forest at Universiti Putra Malaysia Bintulu Campus. These attributes are indispensable growth promoting factors for the planted trees, and natural vegetation thriving amid ongoing threat of soil degradation. Treatment with N-fixing species Burkholderia nodosa NB1 alone resulted in higher root and total N use efficiencies, besides leaves, roots, and total P efficiencies by multiple folds than full chemical fertilizer treatment. Incorporating PGPR isolates with compost and chemical fertilizer proved sustainable in integrated nutrient management (INM) system with minimized usage of chemical fertilizers. Burkholderia nodosa NB1 demonstrates good potential in future field trials before application as bio-fertilizer. Future studies should include more thorough characterization of this particular isolate prior to practical field applications.